Kepemimpinan Cerdas Berbasis AI: Optimalisasi Manajemen Tim di Lingkungan Digital - Rahayu Ningtyas Lestari; Cantika Sayu Ramadhani; Jofite Maulana Rohman; Mochammad Isa Anshori (MASMAN Master Manajemen, 2026)
The development of artificial intelligence (AI) has driven fundamental changes in the way organizations manage work processes, make decisions, and coordinate teams in digital environments. However, an integrated understanding of how AI-based leadership affects digital team performance, particularly through the roles of transformational leadership and digital literacy, remains limited and dispersed across different streams of literature. This study aims to analyze the role of AI in supporting digital leadership, identify its influence on decision-making effectiveness and team performance, and examine the challenges and ethical implications of its implementation in organizations. The study employs a Systematic Literature Review (SLR) approach by reviewing relevant scholarly literature on AI, leadership, digital literacy, human–AI collaboration, and digital team performance. The findings indicate that AI-based leadership can enhance team management effectiveness when implemented through transformational leadership practices that foster vision, change readiness, learning, and team coordination, and when supported by adequate digital literacy. Conversely, barriers such as low trust in AI, digital competency gaps, resistance to change, and ethical issues remain major challenges. This study contributes by offering a conceptual synthesis that positions AI-based leadership, transformational leadership, and digital literacy within a single framework to explain the optimization of digital team performance in modern work environments.